Research Of Certain Peculiarities of Toxic Effects Of 2-Mercaptobenzoiazole on Animals - Farmonov Sirojiddin Nizamovich (Zien Journals, 2022)
The research materials on the toxic effects of 2-Mercaptobenzothiazol on animals are presented. Some parameters of xenobiotic toxicology for white rats, rabbits and karakul sheep are determined. It was established that certain disorders occur during acute and chronic exposure to this drug indicating its negative impact on the body, the immune system and the reproductive function of animals.
Keywords: Mercaptobenzothiazole; rabbits; immune system; reproductive function